Prevalence and Characterization of Enterovirus Infections among Pediatric Patients with Hand Foot Mouth Disease, Herpangina and Influenza Like Illness in Thailand, 2012 - Puenpa, Jiratchaya (Public Library of Science, 2014)
Hand, foot, and mouth disease (HFMD) and herpangina are common infectious diseases caused by several genotypes of human enterovirus species A and frequently occurring in young children. This study was aimed at analyzing enteroviruses from patients with these diseases in Thailand in 2012. Detection and genotype determination of enteroviruses were accomplished by reverse transcription-polymerase chain reaction and sequencing of the VP1 region. Enterovirus-positive samples were differentiated into 17 genotypes (coxsackievirus A4 (CAV4), A5, A6, A8, A9, A10, A12, A16, A21, B1, B2, B4, B5, echovirus 7, 16, 25 and Enterovirus 71). The result showed CAV6 (33.5%), followed by CAV16 (9.4%) and EV71 (8.8%) as the most frequent genotypes in HFMD, CAV8 (19.3%) in herpangina and CAV6 (1.5%) in influenza like illness. Enterovirus infections were most prevalent during July with 34.4% in HFMD, 39.8% in herpangina and 1.6% in ILI. The higher enterovirus infection associated with HFMD and herpangina occurred in infants over one year-old. This represents the first report describing the circulation of multiple enteroviruses in Thailand.